Ocular biometric analysis of cataract surgery candidates, referred from community outreach camps, organized at rural areas of central India - Bhardwaj, Rahul; Jaiswal, Nikita; Sharma, Sandeep; Kohli, Anupriya; Singh, Sindhuja; Pal, Virendra Kumar; Bhadauria, Madhu; Tomar, Vijay Pratap Singh (International Journal Of Community Medicine And Public Health, 2020)
Background: Aim of this study was to analyse the ocular biometric parameters and their associations in a population of cataract surgery candidates. Methods: Ocular biometry records were retrospectively analyzed for 84634 patients with cataracts (84634 eyes) who were treated at Northern Indian region. Ocular biometry characteristics such as Axial length (AL), the Keratometry readings (K1 and K2), and Posterior chamber intraocular lens (PCIOL) power of patients were assessed to find mean, standard deviation, minimum value and maximum value. Statistical analysis was done in Statistical package for social sciences (SPSS) 22.0. Results: Age ranged from 1.0 years to 111 years (mean 63.9±9.24). Males were 43421 (51.3%) and females were 41213 (48.7%). Mean AL was 23.36±3.99 mm. Mean K1 was 44.79± 2.11 D. Mean K2 was 45.05±2.25 D and the average K was 44.92±2.01 D. Significant differences were observed in all the parameters when the findings for females and males were compared. Conclusions: The present study presents normative biometric parameters and their relationships in a rural Indian population. These results may be relevant not only in the evaluation of the refractive error but also in the Intraocular lens (IOL) calculation for cataract surgery. The greatest predictor of the ocular biometrics was age and gender. This would serve as initial normative data for the biometry values in the Indian adults going through cataract surgery because such facts are lacking in Indian population. the rural population.